A pilot study approach on occupational disorders among metal craftsmen of Lalitpur, Nepal - Bhaila, Archana; Joshi, Sunil Kumar; Rajesh Shigdel; Ghosh, Tirthankar (International Journal of Occupational Safety and Health, 2026)
Introduction: Metalcraft is a centuries-old tradition in Lalitpur, Nepal. Workers are exposed to various ergonomic and respiratory risks due to prolonged exposure to metal dust, fumes, and repetitive physical tasks. The present study aims to assess the pulmonary function and musculoskeletal complaints among metal craftsmen, particularly involved in making sculptors . Methods: A pilot cross-sectional study was conducted among 30 metal craftsmen purposively selected in Lalitpur Metropolitan City ward no. 6 and 17. Pulmonary Function Tests (PFT) were performed using a digital spirometer. Musculoskeletal discomfort was assessed using the standardized Nordic Musculoskeletal Questionnaire. Results: 46.6% of metal craftsmen showed signs of respiratory disorders. Significant differences were found in % Predicted FEV1 and FEV1/FVC ratios (p < 0.05) between the different types of work in which metal craftsmen were involved. Lower back discomfort was the most common musculoskeletal complaint, but differences across work types and hours were not statistically significant. Conclusion: Occupational exposure among metal craftsmen may contribute to respiratory impairment. Musculoskeletal issues, although reported, were not significantly associated with work type or duration in this pilot sample. Further research with a larger sample is warranted.